MAIN PHYSIOLOGICAL BUFFALO EXPOSED TO HEAT STRESS AFTER BATH - GONÇALVES, A.M.; ALVES, F.; LALA, B.; BUSTOS MAC LEAN, P.A. (Revista Brasileira de Engenharia de Biossistemas, 2012)
This study aimed to evaluate the time it took buffaloes to return to normal physiological condition after undergoing heat stress. 06 crossbred Murrah buffaloes aged approximately 2.5 to 3.0 years and an average weight of 450 kg were used. The buffaloes were subjected to two treatments with three animals each: bath (B) and without bath (SB). The physiological variables collected were: respiratory rate (RR); sweating rate (SR) and rectal temperature (RT). All animals were kept in a paddock of approximately 2000 m², without the shadow and water tanks, from 8:00 am up to 2:00 pm, for four non-consecutive days of sampling. The samples were taken before and after exposure to the sun, and hourly until 4:00pm. Exposure of animals to the sun made there was a significant increase in physiological parameters to this bath treatment was more efficient to rate, respiratory variable compared to treatment without bath for buffaloes return to its normal state after heat stress.